The people vs global capital the G-7, TNCs, SAPs, and human rights. - Pacific-Asia Resources Center (Tokyo, Japan).; Permanent People's Tribunal; International People's Tribunal to Judge the G-7 (1993 : Tokyo, Japan). (Tokyo, Japan Pacific Asia Resource Center in association with ARENA, Hong Kong, Apex Press, New York, USA, Other India Press, Goa, India, 1994)
Report of Tribunal held in July 1993 as session of the Permanent Peoples' Tribunal coordinated by Pacific-Asia Resources Center.
Keywords: Capitalism -- Developing countries -- Congresses; Developing countries -- Dependency on foreign countries -- Congresses